FUTURE ISLAMIC BANKING: A REVIEW - Erwan Iskandar (Journal Of Resource Management, Economics And Business, 2022)
Purpose: Aims to examine the current state and future prospects of the Islamic banking industry. The study provides a comprehensive overview of the theoretical foundations and practical applications of Islamic finance principles. The research also analyzes the challenges facing the industry and explores potential solutions for sustainable growth in the future. The goal of this study is to provide valuable insights for researchers, policymakers, and industry practitioners in the field of Islamic banking and finance. Research Methodology: literature review with quality journal sources and in-depth examination of the research topic. Results: Examine the current state and future prospects of the Islamic banking industry, provide a comprehensive overview of the theoretical foundations and practical applications of Islamic finance principles, analyze the challenges facing the industry, and explore potential solutions for sustainable growth in the future. The methodology used is a literature review with quality journal sources and in-depth examination of the research topic. The study's contribution includes providing an overview of the current state of the Islamic banking industry. Limitations: The study may have limitations including limited scope, potential availability issues with data and information, potential bias, limited interpretation of Islamic finance principles, and relevance to future developments. It is important to consider alternative perspectives and information sources when interpreting the findings and recommendations of the study. Contribution: Provides an overview of the current state of the Islamic banking industry: The study provides an overview of the current state of the Islamic banking industry, including its size, growth, and market share.